Best anaesthetic drug strategy for morbidly obese patients. Issue 1 (February 2016) - De Baerdemaeker, Luc; Margarson, Michael
Abstract : Purpose of review: The purpose of this review is to describe an evidence-based drug strategy applicable to any obese patient, rather than to present one standard 'ideal' anaesthetic drug combination. The ultimate choice of specific drugs in any given situation will depend upon clinician experience, patient specifics, and drug availability. The fundamental principle in anaesthesia for the obese patient is to use the shortest acting, least fat soluble agents to ensure rapid recovery to safe levels of alertness and mobility. Recent findings: No new drugs have been introduced over the past few years, but we have seen an introduction of enhanced recovery after surgery-based protocols into bariatric surgery. Our understanding of how obesity affects pharmacokinetics/dynamics of our drugs is improving, with new and better use of established drugs. Allometric scaling is being tested in the different pharmacokinetic/dynamic models used in target controlled infusion devices, with improved performance as a result. Obstructive sleep apnoea has a significant impact upon outcome and utilization of clinical resources, including critical care beds. If an improved drug dosing strategy will reduce this impact, then this would be a step forward. Summary: This review introduces newer findings to help us use anaesthetic and analgesic drugs more safely in the morbidly obese. However, there remain many areas of uncertainty with a lack of consensus on many issues.